Active Methodology for the Implementation of Inclusive Education - Muntaner-Guasp, Joan Jordi (2022)
Introduction. Inclusive education is currently consolidated in terms of its approaches and theoretical bases. Still, the implementation of inclusion in ordinary educational centers requires a different performance of the teaching-learning process, which is not yet consolidated. Objective. To determine how the implementation of active methodologies within primary education favors the process of educational inclusion, showing how the presence, participation, and progress of all students can be a reality in schools and classrooms. Methodology. An explanatory qualitative study is described. Eight primary school teachers from different schools in Mallorca participated in the study, with whom six discussion group sessions were held to collect the information. Later, an analysis was conducted with NVIVO data analysis software based on the deductive method. Results. The results show how active methodologies can be inclusive if they attend to certain factors such as the need for a physical and emotional presence linked to the group identity of the classroom, the real participation in planning, communication, and cooperative teams’ processes, and the development of a competency learning. Conclusions. The teaching role and its intervention are highlighted as key elements of good inclusive practices in schools, where the presence, participation, and progress of students are three progressive links of teaching performance and a starting point for improvement and professional development.